Serum alpha-klotho levels associate with bone mineral density in chronic kidney disease patients from NHANES 2011 to 2016 - Yani Zhang; Rui Qi; Xinwei Luo; Jin Lu; Xueying Zhao; Liyuan Wang (Scientific Reports)
Abstract This study investigated the relationship between serum Alpha-Klotho (α-Klotho) levels and bone mineral density (BMD) in patients with chronic kidney disease (CKD) using data from the National Health and Nutrition Examination Survey (NHANES) 2011–2016. A population of 781 CKD patients aged ≥ 40 years was analyzed using multiple linear regression models to examine the association between serum α-Klotho levels and BMD at different skeletal sites, with adjustments for demographic, lifestyle, and clinical factors. Results showed that serum α-Klotho levels were significantly correlated with BMD at thoracic spine (β = 0.004 g/cm2, p = 0.00264), total BMD (β = 0.003 g/cm2, p = 0.02591), and trunk BMD (β = 0.002 g/cm2, p = 0.03708), while no significant associations were observed at the left leg, lumbar spine, or pelvis. Stratified analyses showed that the association was more pronounced in men, non-Hispanic whites, those with a body mass index greater than 29.9 kg/m2, and those without hypertension and diabetes. The inconsistent associations observed across different skeletal sites suggest that it remains unclear whether serum α-Klotho levels are consistently associated with BMD in CKD patients. Additionally, the cross-sectional design precludes any determination of causality in the observed site-specific associations.